2022
DOI: 10.34172/ijhpm.2022.7296
|View full text |Cite
|
Sign up to set email alerts
|

What Might Be Required for Inspections to Be Considered Fair? Comment on "What Lies Behind Successful Regulation? A Qualitative Evaluation of Pilot Implementation of Kenya’s Health Facility Inspection Reforms"

Abstract: Tama et al. offer us an interesting analysis of a piloted regulatory reform that introduced a Joint Health Inspections system in three Kenyan counties. The study highlights key factors facilitating or hindering the implementation of the reform. In this commentary we reflect on the concept of fairness, which is one of the topics that is discussed in the study. We describe four important dimensions of fairness in the context of inspections: expectation clarity, consistency of assessment, consistency of enforceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated that a proper regulatory design may provide a fair and broad assessment of the complexity involved in the case 9 15 36 37. Involvement of several stakeholders in the process may serve as a way of restoring trust between the healthcare provider and the patient or next of kin, as well as reinforcing the public’s trust in the health services altogether 9 38–45.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that a proper regulatory design may provide a fair and broad assessment of the complexity involved in the case 9 15 36 37. Involvement of several stakeholders in the process may serve as a way of restoring trust between the healthcare provider and the patient or next of kin, as well as reinforcing the public’s trust in the health services altogether 9 38–45.…”
Section: Discussionmentioning
confidence: 99%